Armed Forces, Cyberspace, and Global Images: The Official Website of the Israeli Defense Forces 2007–2015. Issue 2 (April 2018) - Golan, Oren; Ben-Ari, Eyal
This study centers on the relation between militaries, violence, and publicly available digital images. Military websites can be characterized as forms of representation of national institutions comparable to the sites of any large organization. However, the way these websites publicly frame and explain the military's use of organized violence has not been investigated. Accordingly, this study examines how contemporary militaries manage their public and online relation to their core expertise, organized violence. The analysis is based on a longitudinal analysis of the Israeli Defense Force's (IDF) official websites (2007–2015) and interviews with key webmasters. The integration of the Internet and new media into the IDF's official websites highlights its deliberate move into the cybernetic realm to manage, order, manipulate, and handle its public images and representations as a legitimate social institution charged with using violence in the defense of the country.